Internet Shop - As a Promising Direction for the Development of Retail Trade Services - Tashmatov, Sharaf Urokboevich (Research Parks Publishers, 2023)
The article analyzes the definitions of the concept of an internet shop, examines the main elements, types and classification of an internet shop by means of earnings.